Pengaruh E-Learning Berbasis Aplikasi Google Classroom dalam Pembelajaran Pendidikan Agama Kristen terhadap Hasil Belajar Siswa Kelas VIII di SMP Kristen Palangka Raya - Rahmelia, Silvia; Agustina, Maria; Rudie (Harati: Jurnal Pendidikan Kristen, 2022)
Google Classroom is very popular nowadays, especially during this remote learning due to Covid-19 pandemic. However, the effectiveness of its use has yet to be ascertained on students' learning result, including in Christian Religious Education learning process. This research was conducted at Palangka Raya Christian Middle School with the research purpose is to find out how much e-learning based on Google Classroom application in Christian Religious Education learning has effect on learning outcomes. Research method that used is non-experimental quantitative with a comparative causal type of research, so this method is to examine cause-and-effect relationships. The population in this research were all students in Palangka Raya Christian Middle School, i.e 104 students, while the sample used was 34 students at eighth grade. The results showed that there was an effect of e-learning based on the google classroom application in learning Christian Religious Education, towards learning outcomes of students at Palangkaraya Christian Middle School with a significance level of 0.249 > 0.05. This effect is relatively small with an R Square value of 41%. That is, the learning outcomes of eighth grade students at Palangka Raya Christian Middle School are more influenced by other variables in improving student learning outcomes. Aplikasi google classroom sangat populer digunakan saat ini, terlebih di tengah sistem pembelajaran jarak jauh sejak pandemi Covid-19. Namun demikian efektivitas penggunaannya belum dapat dipastikan terhadap keberhasilan belajar peserta didik, termasuk dalam pembelajaran Pendidikan Agama Kristen. Penelitian ini dilakukan di SMP Kristen Palangka Raya dengan tujuan untuk mengetahui seberapa besar pengaruh e-learning berbasis aplikasi google classroom dalam pembelajaran Pendidikan Agama Kristen terhadap hasil belajar siswa kelas VIII di SMP Kristen Palangka Raya. Metode penelitian yang digunakan adalah kuantitatif non-eksperimen dengan jenis penelitian kausal komparatif untuk meneliti hubungan sebab-akibat. Populasi pada penelitian ini adalah seluruh siswa di SMP Kristen Palangka Raya yang berjumlah 104 siswa, sedangkan untuk sampel yang digunakan adalah 34 orang. Hasil penelitian menunjukkan bahwa adanya pengaruh e-learning berbasis aplikasi google classroom dalam pembelajaran Pendidikan Agama Kristen terhadap hasil belajar siswa kelas VIII di SMP Kristen Palangka Raya dengan taraf signifikasi sebesar 0,249 >̲ 0,05. Adapun pengaruh tersebut terbilang kecil dengan nilai R Square sebesar 41%. Artinya, hasil belajar siswa kelas VIII di SMP Kristen Palangka Raya lebih besar dipengaruhi oleh variabel lain dalam meningkatkan hasil belajar siswa.